2016
DOI: 10.4236/tel.2016.61009
|View full text |Cite
|
Sign up to set email alerts
|

On the Linkages between India VIX and US Financial Stress Index

Abstract: The present study is the first of its kind accounting for linkages among India VIX and US financial stress index by employing vector autoregression model (VAR), Granger causality test, generalized impulse response functions, variance decomposition analysis (VDA) and Diebold and Yilmaz's (2009) spillover index highlighting the impact of cross market variations on each other. The span of monthly data ranges from 2009 to 2015, particularly after the global financial crisis. The results report a unidirectional cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Furthermore, e i is m x1, with ith element equal to one and all other elements equal to zero. The GIRF for a one standard deviation shock to the ith equation in the VAR model on the jth variable at horizon N is defined as (Ewing and Wunnava, 2004; Singh, 2016): …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, e i is m x1, with ith element equal to one and all other elements equal to zero. The GIRF for a one standard deviation shock to the ith equation in the VAR model on the jth variable at horizon N is defined as (Ewing and Wunnava, 2004; Singh, 2016): …”
Section: Methodsmentioning
confidence: 99%
“…Finally, since financial markets are interconnected and stock market price volatility can also be impacted by the stress of the whole financial market (Das et al, 2019 ; Gupta et al, 2014 ; Singh, 2016 ; Sum, 2014 ). As the result of global economic integration, the stock markets of individual countries are subject to the stress of both the financial market of that country and the global financial market (Das et al, 2019 ; Singh, 2016 ). So, we further consider 2 financial stress indicators: (14) the financial stress index provided by the Office of Financial Research (OFRFSI); (15) the financial stress index provided by St. Louis Fed.…”
Section: Datamentioning
confidence: 99%
“…In addition, studies have found evidence that the stock market can be driven by investors’ psychology (Daniel et al, 2002 ; Tseng, 2006 ) and determined the predictive power of some market sentiment indicators (see, e.g., Gupta et al, 2014 ; Perez-Liston et al, 2014 ; Oliveira et al, 2017 ; Jin et al, 2020 ; Liang et al, 2020a ; Wang et al, 2020a ). Other indicators, such as financial stress indices, have also been proven to have potential forecasting ability (Gupta et al, 2014 ; Singh, 2016 ; Sum, 2014 ). The predictive abilities of these potential predictors tend to change with changes in various external factors, making it more difficult to find stable predictors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation